2004
DOI: 10.1007/978-3-540-30212-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Structure of Degeneracy for Multi-body Motion Segmentation

Abstract: Abstract. Many techniques have been proposed for segmenting feature point trajectories tracked through a video sequence into independent motions. It has been found, however, that methods that perform very well in simulations perform very poorly for real video sequences. This paper resolves this mystery by analyzing the geometric structure of the degeneracy of the motion model. This leads to a new segmentation algorithm: a multi-stage unsupervised learning scheme first using the degenerate motion model and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 14 publications
0
79
0
Order By: Relevance
“…The Multi-Stage Learning (MSL) algorithm is a statistical approach proposed by Sugaya and Kanatani in [14]. It builds on Costeira and Kanade's factorization method (CK) [3] and Kanatani's subspace separation method (SS) [10,11].…”
Section: Multi-stage Learning Methods (Msl) [14]mentioning
confidence: 99%
See 2 more Smart Citations
“…The Multi-Stage Learning (MSL) algorithm is a statistical approach proposed by Sugaya and Kanatani in [14]. It builds on Costeira and Kanade's factorization method (CK) [3] and Kanatani's subspace separation method (SS) [10,11].…”
Section: Multi-stage Learning Methods (Msl) [14]mentioning
confidence: 99%
“…For example, when two objects have the same rotational but different translational motion relative to the camera [14], or for articulated motions [20]. This has motivated the development of several algorithms for dealing with partially dependent motions, including statistical methods [6,14], spectral methods [21,22] and algebraic methods [16].…”
Section: Segmentation Of Multiple Rigid-body Motionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches have been proposed which can be categorized into factorization based [22,23], clustering based [7,13], robust estimation based [9,17,5,19], algebraic [25] and statistical methods [20,11]. A brief review of most of these techniques can be found in [7].…”
Section: Projective Motion Segmentationmentioning
confidence: 99%
“…[25]. Older methods such as LSA [23], ALC [10] MSL [16], GPCA [22] and RANSACtype subspace fitting approaches have since been surpassed. Of course, one is not limited to subspace methods for solving the motion segmentation problem, or indeed an affine camera model.…”
Section: Introductionmentioning
confidence: 99%